ANALISIS FAKTOR KEPUASAN, KEPERCAYAAN DAN LOYALITAS KONSUMEN PADA BELANJA ONLINE - Devi Amaliya Putri; Rizky Maulida (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2023)
The internet is one of the most important communication technology media in human life at this time. The internet is able to expand the network and interaction between humans with one another through the means of a medium. Economic growth in Indonesia is in the online shopping sector (online shop), as evidenced by the many new online shops that keep popping up. Online shopping or online shopping has now become a new way for some Indonesians to shop. Almost all items are offered through online shops which are currently very popular with teenagers, from clothes, accessories, watches, shoes, even food, which are also offered online. And also the many cases of fraud committed by sellers with the Online Shop mode. Satisfaction, trust and loyalty of consumers is very important for the company, this must be very concerned for the company. After looking at several explanations regarding customer satisfaction, trust and loyalty, the authors can draw an understanding that satisfied consumers based on their previous experience will make repeat purchases, because consumers can feel the product they bought is in accordance with the form that consumers expected before.